ANALISIS KESALAHAN SEMANTIK PADA ARTIKEL OPINI KOMPASIANA EDISI MARET 2025 - Khoeriyah, Saniatul; Casim, Casim (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2025)
Semantic errors in opinion articles can occur due to a lack of precision, mistakes, or the author's ignorance regarding the correct writing conventions, resulting in unclear meanings or ambiguous interpretations. This study aims to analyze semantic errors in opinion articles published in Kompasiana in March 2025. The method employed is qualitative research. The data used in this study consists of words and sentences from opinion articles published in Kompasiana March 2025 edition that contain semantic errors. The source of the research data is opinion articles published by Kompasiana. Data collection techniques involve carefully reading the opinion articles and noting the semantic errors that occur. Data analysis techniques are employed to analyze the data and draw conclusions. The results and discussion encompass semantic errors found in the opinion articles of Kompasiana's March 2025 edition. The analysis revealed 17 instances of linguistic errors at the semantic level due to inappropriate word choice and diction, hypercorrection phenomena, pleonasm, and ambiguity. Keywords: Semantic Errors, Opinion Articles, Kompasiana.